Environmental Peacebuilding and Solar Geoengineering - Buck, Holly Jean (Frontiers in Climate, 2022)
Solar geoengineering, or reflecting incoming sunlight to cool the planet, has been viewed by international relations and governance scholars as an approach that could exacerbate conflict. It has not been examined through the framework of environmental peacebuilding, which examines how and when environmental challenges can lead to cooperation rather than conflict. This article argues that scholars should treat the link between solar geoengineering and conflict as a hypothesis rather than a given, and evenly examine both hypotheses: that solar geoengineering could lead to conflict, and that it could lead to peace. The article examines scenarios in which geoengineering may lead to negative peace — peace defined as the absence of conflict — and then applies a theoretical framework developed by environmental peacebuilding scholars to look at how solar geoengineering could relate to three trajectories of environmental peacebuilding. A peace lens for solar geoengineering matters for research and policy right now, because focusing narrowly on conflict in both research and policy might miss opportunities to understand and further scenarios for environmental peacebuilding. The paper concludes with suggestions for how research program managers, funders, and policymakers could incorporate environmental peacebuilding aims into their work.